Our Nanotechnology Future - Natowitz, Joseph (Atlantis Advances in Nanotechnology, Material Science and Energy Technologies, 2017)
This book explores nanotechnology, a rapidly evolving and growing field with applications in a large number of areas. The concepts and physics are highlighted through topics such as nanoscience, quantum effects, nanostructures, and new forms of carbon. Applications and potential health and safety implications of nanomaterials are discussed for healthcare, food production, electronics, defence and more. Accessible and timely, this introduction to nanotechnology will interest students, teachers, politicians, and everyone else eager to learn more about this dynamic field.